2015
DOI: 10.1148/radiol.2015142029
|View full text |Cite
|
Sign up to set email alerts
|

Unresectable Adrenal Metastases: Clinical Outcomes of Radiofrequency Ablation

Abstract: Adrenal RF ablation is a feasible and useful method for controlling adrenal metastases and offers patients opportunities for improved survival.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
93
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 67 publications
(99 citation statements)
references
References 32 publications
5
93
1
Order By: Relevance
“…The first step is the confirmation or the exclusion of the diagnosis of AM: in the recent years the combination of high resolution CT and PET scans has proved to be very accurate in distinguishing benign from malignant adrenal masses (13,24); the use of FNAC is rarely needed in indeterminate cases (25). Notwithstanding the reliability of pre-operative imaging in excluding the benign nature of the mass, a basic functional evaluation is warranted, especially in order to exclude pheochromocytoma (8,26), perhaps essential also if the treatment choice is radiofrequency ablation of the mass (27,28).…”
Section: Discussionmentioning
confidence: 99%
“…The first step is the confirmation or the exclusion of the diagnosis of AM: in the recent years the combination of high resolution CT and PET scans has proved to be very accurate in distinguishing benign from malignant adrenal masses (13,24); the use of FNAC is rarely needed in indeterminate cases (25). Notwithstanding the reliability of pre-operative imaging in excluding the benign nature of the mass, a basic functional evaluation is warranted, especially in order to exclude pheochromocytoma (8,26), perhaps essential also if the treatment choice is radiofrequency ablation of the mass (27,28).…”
Section: Discussionmentioning
confidence: 99%
“…The objective response rate (technical effectiveness) and median survival duration were 100% and 24.9 months, respectively [17]. However, another recent study [19] involving four cases observed a median survival duration of only 9.3 months, which is significantly different from that in abovementioned study. This discrepancy can be attributed to the intrahepatic tumor status, which is an important factor influencing the overall outcomes of patients with EHM [21].…”
Section: Discussionmentioning
confidence: 62%
“…Sohn et al reported that the tumor response rate for sorafenib treatment in patients with HCC and EHM was 5% (complete response: 0%, partial response: 5%), with a median survival duration of 11.9 months for patients with adrenal metastases [30]. Previous studies have shown that local treatments for metastases achieve better control and outcomes, with survival durations of 12 to 21.4 months and 9.3 to 24.9 months after adrenalectomy and thermal ablation, respectively [9,10,17,19]. Our results support this theory by showing that local treatment may be effective in controlling limited metastases from HCC, and that patients with unresectable metastatic tumors are potential candidates for ablation therapy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…RFA is not advisable for large lesions and those that are suspected to be malignant on imaging. Although RFA is potentially applicable to malignant adrenal conditions, its use in patients with potentially curative primary adrenocortical carcinoma should be strongly discouraged.…”
Section: Discussionmentioning
confidence: 99%